Expansion of seasonal influenza vaccination in the Americas - Ruiz-Matus Cuauhtémoc; Danovaro-Holliday M Carolina; Kurtis Hannah J; Ropero-Álvarez Alba; Andrus Jon K (BMC, 2009)
Abstract Background Seasonal influenza is a viral disease whose annual epidemics are estimated to cause three to five million cases of severe illness and 250,000 to 500,000 deaths worldwide. Vaccination is the main strategy for primary prevention. Methods To assess the status of influenza vaccination in the Americas, influenza vaccination data reported to the Pan American Health Organization (PAHO) through 2008 were analyzed. Results Thirty-five countries and territories administered influenza vaccine in their public health sector, compared to 13 countries in 2004. Targeted risk groups varied. Sixteen countries reported coverage among older adults, ranging from 21% to 100%; coverage data were not available for most countries and targeted populations. Some tropical countries used the Northern Hemisphere vaccine formulation and others used the Southern Hemisphere vaccine formulation. In 2008, approximately 166.3 million doses of seasonal influenza vaccine were purchased in the Americas; 30 of 35 countries procured their vaccine through PAHO's Revolving Fund. Conclusion Since 2004 there has been rapid uptake of seasonal influenza vaccine in the Americas. Challenges to fully implement influenza vaccination remain, including difficulties measuring coverage rates, variable vaccine uptake, and limited surveillance and effectiveness data to guide decisions regarding vaccine formulation and timing, especially in tropical countries.